PENGARUH PENGUASAAN KECEPATAN TERHADAP HASIL BELAJAR FISIKA MATERI POKOK MOMENTUM DI KELAS XI SMA NEGERI - Febriani Hastini Nasution (JURNAL PhysEdu (PHYSICS EDUCATION), 2024)
The aims of this study was to see thesignificant effect theeffect of speed mastery to studentlearning achievementof thePhysic on material of momentum at eleventh grade of SMA Negeri. The method of the research was descriptive method and correlation method. The population was the eleventh grade students of science at SMA Negeri. It divided in three parallel class consists of 132 students. Random sampling technique was done in this research. The sample of this research consists of 45 students. In analyzing the data, the researcher used descriptive analysis and inferential analysis. The average score of speed mastery was 74.62 in “good” category. While studentlearning achievementof the Physic on material of momentum was 81.03 in “Very Good” category. Based on the analysis of the data, the average score of. rcount was 08.48. While rtable was 2.02. It means that the rcount was higher than rtable ( 81.03>2.02). In other words the hypothesis of this research was accepted. It means that there was the Effect of speed mastery to studentlearning achievementof the Physic on material of momentumat eleventh grade of SMA Negeri.